Administracion

Solo disponible en BuenasTareas
  • Páginas : 59 (14688 palabras )
  • Descarga(s) : 6
  • Publicado : 12 de abril de 2010
Leer documento completo
Vista previa del texto
21.

(a − 2b)
2

3a

2

+

5 1 + a − 5b a − 2b
2

23.

1 1 1 − − + 3x − 9 6 x + 12 2 ( x − 3)2 =

1 x − 6+ 9 x

3a − 14ab + 10b a 2 − 4ab + 4b2

3a (a − 5b) + 5 (a − 2b) + (a − 2b)(a − 5b)
2

x 1 1 1 − − 2 + x 2 − 6x + 9 3 ( x − 3) 6 ( x + 2) 2 ( x − 3)
2

=

3a 2 − 14ab + 10b 2

(a − 2b) (a − 5b)
2

= =

2 ( x − 3)( x + 2) − ( x − 3) − 3( x + 2) + 6 ( x + 2)6 ( x − 3) ( x + 2)
2 2

(a − 2b)
2 2

2 2 2 2

2 x 2 − 2 x − 12 − x 2 + 6 x − 9 − 3x − 6 + 6 x 2 + 12 x 6 ( x − 3) ( x + 2) 7 x 2 + 13x − 27
2

= =

3a − 15ab + 5a − 20ab + 20b + a − 7ab + 10b
2 2

(a − 5b)(3a
2

− 14ab + 10b 2 ) =

=
2

(a − 5b)(3a

9a − 42ab + 30b
2

− 14ab + 10b2 )

3(3a − 14ab + 10b ) 3 = (a − 5b)(3a − 14ab + 10b ) a − 5b
2 2 2

6 ( x − 3) (x + 2)

x+1 − x−1 22. x − 1 + x+1

x−1 x + 1 x2 + 1 2x ⋅ ÷ x + 1 2a 2 − 2b a 2 − b x−1
2 2

a 2 + b2 b2 a+b b+ a 1 ⋅ ⋅ 24. 2a − b a 2 − 2b 2 a − b 1+ a+b− b a−b a−b+ a 2 − b 2 + a 2 + b 2 ab + b 2 a+b 1 = 2 ⋅ a ⋅ a − b 2 − a 2 + 2b 2 a − b b + 2a − b b a−b
2

(x + 1) − (x − 1)
= x2 − 1
2

(x − 1) + (x + 1)
x2 − 1
2 2

2



a2 − b 2 (a − b) 2 x
2

x2 + 1



=

x + 2x + 1− x + 2 x − 1 x + 1 x +1 1 4x ⋅ = ⋅ = x 2 − 2 x + 1+ x2 + 2 x + 1 4 x 2 2 ( x 2 + 1) 4 x
2

2a 2 b (a + b) 2 a+b 1 2a (a − b) b (a + b) b a ⋅ = ⋅ ⋅ =1 = 2 ⋅ 2a b 2 (a + b) a (a − b) 2a b a−b b a−b

EJERCICIO 141
1.

x 1 + 5= − x 6 3 x + 30 1 − 3x ⇒ = 6 3

4. 2 + 2 − 12 = 6 − 4

x

x

x

5

mcm = 12

7.

6 x + 24 − x = 2x − 15 6 x − x − 2x = − 15 − 24 3x = − 39 − 39 x=3 x = − 13

x−4 −5=0 3 x − 4 − 15 = 0 x − 19 = 0 x = 19

mcm = 3

x + 30 = 2 (1 − 3x )

x + 30 = 2 − 6 x x + 6 x = 2 − 30 7 x = − 28 − 28 x= 7 x=−4 3x 2x 1 − + = 0 mcm = 15 2. 5 3 5 9x − 10x + 3 = 0 −x=−3 x=3 1 1 1 1 mcm = 20x + − = 3. 2x 4 10x 5 10 + 5 x − 2 = 4x 5x − 4 x = − 10 + 2 x=−8

8. x −

5.

3x 1 5 3x − + 2x = − mcm = 20 4 5 4 20 15x − 4 + 40x = 25 − 3x 55x + 3x = 25 + 458x = 29

x + 2 5x = mcm = 12 12 2 12x − x − 2 = 30x 11x − 30x = 2 − 19x = 2 x=− 2 19

29 x= 58 1 x= 2 2 5 7 3 − = − + 1 mcm = 30x 6. 3x x 10 2x 20 − 150 = 21x − 45 + 30x − 130 + 45 = 51x − 85 =x 51 −5 =x 3

9. x −

5x − 1 3 = 4x − mcm = 15 3 5 15x − 25x + 5 = 60x − 9 − 10x − 60x = − 9 − 5 − 70x = − 14 − 14 − 70 1 x= 5 x=

10. 10 x −

40 x − 8 x + 3 = 8 ( x − 3)

8x − 3 = 2 ( x − 3)mcm = 4 4

15. 4 −

40 x − 8x = 8 x − 24 − 3 40 x − 16 x = − 27 − 27 x= 24 9 x= − 8
11.

48 − 2 (10 x + 1) = 48 x − 3 (16 x + 3) 48 − 20 x − 2 = 48 x − 48 x − 9 − 20 x + 46 = − 9 − 20 x = − 55 − 55 x= − 20 11 x= 4
1 1 1 16. 2 ( x − 1) − ( x − 3) = 3 ( x + 3) + 6 3x − 3 − 6x + 18 = 2 x + 6 + 1 − 3x + 15 = 2 x + 7 − 5x = − 8 x= 8 5 mcm = 36 mcm = 6

10 x + 1 16 x + 3 = 4x − 6 4

mcm = 1220 ( x − 2) − 15 (x − 3) = 12 ( x − 4) 20 x − 40 − 15x + 45 = 12 x − 48 5x − 12 x = − 48 − 5 − 7 x = − 53 53 x= 7 x−1 x− 2 x− 3 x−5 − − =− 12. 2 3 4 5 mcm = 60

x− 2 x−3 x− 4 − = mcm = 60 3 4 5

3( x − 1) − 6 ( x − 3) = 2 ( x + 3) + 1

30 ( x − 1) − 20 ( x − 2) − 15( x − 3) = − 12 ( x − 5) 30x − 30 − 20 x + 40 − 15x + 45 = − 12 x + 60 − 5x + 55 = − 12 x + 60 − 5x + 12 x = 60 − 55 7x = 55 x= 7

17.

12 (6 x + 1) − 4 (11x − 2) − 9 (5x − 2) = 30 (6 x + 1) 72 x + 12 − 44 x + 8 − 45x + 18 = 180 x + 30 − 17 x + 38 = 180 x + 30 − 197 x = − 8 x= 8 197 mcm = 6

6x + 1 11x − 2 1 5 − − (5x − 2) = (6 x + 1) 3 9 4 6

13. x − 5x − 1 −

(

)

10 x − 10 (5x − 1) − (7 − 5x) = 10

7 − 5x = 1 mcm = 10 10
18.

10 x − 50 x + 10 − 7 + 5x = 10 − 35x + 3 = 10 − 35x = 7 −7 x= 35 1 x=− 5
14. 2 x −

2 (4 x + 1) = 2 (4 x − 1) − (13 + 2 x ) − 3( x − 3) 8 x + 2 = 8 x − 2 − 13 − 2 x − 3x + 9 2 = − 6 − 5x 8 = − 5x − 8 =x 5 mcm = 10

4x + 1 1 13 + 2 x 1 = (4 x − 1) − − ( x − 3) 3 3 6 2

5x − 6 1 + ( x − 5) = − 5x 4 3 mcm = 12

19.

24 x − 3(5x − 6) + 4 ( x − 5) = − 60 x 24 x − 15x + 18 + 4 x − 20 = − 60x 13x − 2 = − 60x 13x + 60x = 2 2 x= 73

4 (5x − 1) + 3 (10x − 3) =...
tracking img